Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s12649-016-9512-6
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Nixtamalization Waste Waters Clarified by Ultrafiltration for Production of a Fraction Rich in Phenolic Compounds

Abstract: Clarified nixtamalization waste waters rich in calcium and polyphenols were subjected to ultrafiltration. The effluent was analyzed for its concentration of soluble solids, total solids content, pH, conductivity, turbidity, density, polyphenols, carbohydrates, total organic carbon, calcium content, and antioxidant activity. The operating conditions were as follows: transmembrane pressure 172 kPa, feed flow rate 58 L h -1 , and temperature 25°C. We analyzed the separation process for water permeability, fouling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The fouling index of the membrane was about 77.9% by the treatment (see Table ), the index was higher than reported by Cassano, Donato, et al () for ultrafiltration of kiwifruit juice (32%). The membrane fouling of this study is similar than reported in other studies aiming the treatment of agro‐food by‐products by ultrafiltration, that is, Conidi, Cassano, and Drioli (), Castro‐Muñoz and Yáñez‐Fernández (), and Castro‐Muñoz, Barragán‐Huerta, and Yáñez‐Fernández () determined fouling indexes of 73.8, 87.0, and 91.7% in the recovery of phenolic compounds, carbohydrates and polyphenols from orange press liquor, maize extracts, and maize cooking waters, respectively. The membrane fouling (as well as the membrane performance) are influenced by different key factors such as physicochemical composition (organic matter) of the bulk solution, concentration polarization phenomenon, effects of adsorption (solute–solute and solute–membrane), membrane characteristics (MWCO, configuration module, material, hydrophobicity, porosity, and surface charge), electrostatic interactions, and operating conditions (TMP, flow rate, and temperature) (Boussu et al, ; Salahi et al, ; Xiao, Xiao, Zhang, & Wang, ).…”
Section: Resultssupporting
confidence: 88%
“…The fouling index of the membrane was about 77.9% by the treatment (see Table ), the index was higher than reported by Cassano, Donato, et al () for ultrafiltration of kiwifruit juice (32%). The membrane fouling of this study is similar than reported in other studies aiming the treatment of agro‐food by‐products by ultrafiltration, that is, Conidi, Cassano, and Drioli (), Castro‐Muñoz and Yáñez‐Fernández (), and Castro‐Muñoz, Barragán‐Huerta, and Yáñez‐Fernández () determined fouling indexes of 73.8, 87.0, and 91.7% in the recovery of phenolic compounds, carbohydrates and polyphenols from orange press liquor, maize extracts, and maize cooking waters, respectively. The membrane fouling (as well as the membrane performance) are influenced by different key factors such as physicochemical composition (organic matter) of the bulk solution, concentration polarization phenomenon, effects of adsorption (solute–solute and solute–membrane), membrane characteristics (MWCO, configuration module, material, hydrophobicity, porosity, and surface charge), electrostatic interactions, and operating conditions (TMP, flow rate, and temperature) (Boussu et al, ; Salahi et al, ; Xiao, Xiao, Zhang, & Wang, ).…”
Section: Resultssupporting
confidence: 88%
“…Valderrama‐Bravo and others () showed that during nixtamalization, clusters of calcium carbonate and calcite are formed. Even after ultrafiltration using 1 kDa membranes, 17% of these calcium forms along with calcium hydroxide used for lime cooking remain in the effluent (Castro‐Muñoz and others ).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that UF could be an alternative process for clarification and sterilization. UF has been used to clarify nixtamalization waste waters for the recovery of phenolic compounds [57]. In our study, the 3 kDa UF process slightly decreased the amount of piceid and resveratrol, but the concentration of piceid and resveratrol did not change by the 10 kDa UF process.…”
Section: Resultsmentioning
confidence: 55%